Pengembangan e-modul pembelajaran IPA berorientasi etnosains alat musik pada materi gelombang bunyi untuk meningkatkan kemampuan berpikir kritis peserta didik - Riska, Dara; Mayub, Afrizal; Karyadi, Bhakti (PendIPA Journal of Science Education, 2024)
This study aims to develop ethnoscience-oriented science learning e-modules on sound waves of musical instruments improve the critical thinking skills of junior high school students in Bengkulu City. The research method used is R&D with the ADDIE model which are Analysis, Design, Development, Implementation , and Evaluation. This research was conducted on 33 students of eighth grade junior high school 2 Bengkulu City by using pretest-posttest design method. The results showed that: 1) Students stated that it is necessary to develop ethnoscience electronic modules (e-modules) to improve critical thinking skills in science learning. 2) The results of expert and practitioner validation of e-module feasibility instruments consist of four aspects, namely aspects of graphics, media aspects, language feasibility aspects, presentation feasibility aspects, and content feasibility aspects were declared feasible with an average percentage of 87.20% 3) The results of expert and practitioner validation of critical thinking skills instruments consisting of elementary clarification, basic support, inference, providing advance clarification, and organizing strategies and tactics were declared feasible with an average percentage of 93.33% . 4) There is an increase in students' critical thinking skills after using e-modules with a moderate category and a significance value of <0.05 is obtained, meaning that there is a significant effect with the use of sound wave ethnoscience e-modules in improving students' critical thinking skills.5) Students' response to the sound wave ethnoscience e-modules developed in the science learning process reached a percentage of 90.79%. with a very good category.